Relationship between circumcision scar thickness, postcircumcision mucosal cuff length measures and premature ejaculation. (August 2012) - Tarhan, Huseyin; Can, Ertan; Akdeniz, Firat; Akarken, Ilker; Cakmak, Ozgur; Zorlu, Ferruh
Abstract Objective. The etiology of premature ejaculation (PE) is unknown. Over the past two decades several studies have suggested that lifelong and acquired PE may be caused by somatic disorders and/or neurobiological disturbances. One controversial factor is the effect of circumcision on ejaculation. This prospective study investigated the relationship between postcircumcision penile mucosal cuff length, circumcision scar thickness and the PE syndromes. Features of PE patients were compared with those of a normal healthy control (NHC) group. Material and methods. In total, 160 circumcised men were studied: 80 men with PE and 80 men in the NHC group. The following data and measurements were evaluated: age, type of PE syndrome, intravaginal ejaculation latency time (IELT), circumcision scar thickness and postcircumcision mucosal cuff length. Results. In terms of the mean IELT, a statistically significant difference was detected between the PE syndromes (p < 0.05), and between the PE patients and the control group (p < 0.05). Among the four PE syndromes, there was no significant difference related to the mean mucosal cuff length and mean circumcision scar thickness (p > 0.05). No significant difference was observed between the two groups for mean mucosal cuff length (p > 0.05) or mean circumcision scar thickness (p > 0.05). Conclusion. In this study, no relationship was observed between PE and postcircumcision penile mucosal cuff length and circumcision scar thickness. Further studies are required to evaluate the positive and negative effects of circumcision on PE syndromes.